Electrical and gas sensing properties of Li and Ti codoped NiO/PVDF thin film - (:unkn) unknown (ELSEVIER SCIENCE SA, 2009)
In this study the electrical and gas sensing properties of Li and Ti codoped NiO (LTNO)/polyvinylidenefluoride (PVDF) nanocomposites were investigated. LTNO with a composition of Li0.1Ti0.018Ni0.882O was prepared using citrate-gel technique. Phase evolution of as-prepared and calcined powders were examined by XRD technique and single phase NiO was obtained at 500,C. TEM investigation revealed that the size of particles ranged from 5 to 40 nm. Thin films of LTNO/PVDF nanocomposite were synthesized using spin coating method. The electrical properties of film were investigated as a function of temperature. It was observed that the In sigma(dc)-1/T graph consists of two different linear regions. While room temperature impedance spectra of film consist of a curved line, a transformation into a full semicircle with increasing temperature was observed from the complex plane plots of impedance. From the analysis of frequency, f, dependence of electrical conductivity, (T,,, it was found that the sigma(ac) obeys the power law given by sigma(ac) = sigma(0)omega(5), in which the frequency exponent s decreases with temperature. The sensing properties of the film for NH3 were also investigated. It was observed that the conductivity (dc and ac) strongly dependent on the presence of the NH3 gas. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Nanocomposite; Citrate-gel processing; Gas sensors; Electrical properties; PVDF; SURFACE MODIFICATION; DOPED NIO; CERAMICS; SENSORS; TEMPERATURES; LIXNI(1-X)O; CONDUCTION; NO2